Analysis and influence of the underwater phase of breaststroke on short-course 50 and 100m performance - Sánchez, L.; Arellano, R.; Cuenca-Fernández, F. (International Journal of Performance Analysis in Sport, 2021)
The aim was to analyse the influence of the breaststroke underwater phase on 50 and 100 m performance. A total of 108 performances in 50 m (61 males and 47 females), and 126 performances in 100 m (71 males and 55 females) were recorded during the 2019 Short-course National Spanish Championship. The underwater swimming time, distance and velocity were analysed after the start and turns. Pearson correlation coefficients (r) and regression analysis were applied to compute the relation between the variables. The relative contribution (%) to final time and the differences between events and gender were studied through independent samples t-test (p < 0.05). High correlations were obtained for both events and genders between start time and final time (r = 0.76-0.91). The emersion velocity was higher in 50 m than in 100 m (p < 0.001; d > 1.0) and in males (50 m: 2.18 ± 0.10 m·s-1; 100 m: 1.87 ± 0.08 m·s-1) than in females (50 m: 1.92 ± 0.09 m·s-1: 100 m: 1.71 ± 0.08 m·s-1). Performance in both events was influenced significantly by turn velocity (r = -0.85), and combined with the start, contributed to around 55% of the final time. Coaches should optimise the underwater phases of start and turns on breaststroke performance in short-course.